Friend or foe? Bilateral political relations and the portfolio allocation of foreign institutional investors - Lugo, Stefano; Montone, Maurizio (Journal of Corporate Finance, 2026)
We study the role of bilateral political relations in explaining variations in the equity portfolio allocation of foreign institutional investors. Using a large sample at the fund–firm–year level, we find that political distance between countries leads to significant retrenchment of foreign institutional investors from local firms. Consistent with our theorized mechanisms, we find that the effect is stronger for stocks that are more exposed to geopolitical risk, dividend-paying, and less liquid, as foreign investors sell off local securities perceived to become riskier to hold. Overall, our findings identify a novel financial channel through which geopolitical risk affects international equity markets.